Corrosion Monitoring of Galvanized Steel in Simulated Wet-Dry Cyclic Condition in 0.05 M NaCl Solution - Yadav, AP (Scientific World, 2010)
The corrosion monitoring of galvanized steel in 1 h wet and 7 h dry cyclic condition in 0.05 M NaCl has been carried out using AC impedance technique. During the wet-dry cycles, the polarization resistance, Rp, and solution resistance, Rs, were continuously monitored. The instantaneous corrosion rate of the coating was estimated from the obtained Rp-1 and time of wetness (TOW) was determined from the Rs values. The corrosion potential, Ecorr, was measured twice a day during the immersion period of wet-dry cycle. The corrosion was accelerated by the wet-dry cycles in the early stage followed by a decrease in the final stage of wet-dry cycle. The corrosion potential shifted to more negative direction for the first 8 cycles due to dissolution of air formed oxide. A gradual shift in the corrosion potential with the progress of corrosion in the later stage of the wet-dry cycle was observed due to deposition of corrosion products. The corrosion mechanism of galvanized steel is discussed based on the results of corrosion monitoring and corrosion potential variation. Key words: Atmospheric corrosion; Galvanized steel; AC Impedance; Corrosion rate. DOI: 10.3126/sw.v8i8.3855 Scientific World Vol.8(8) 2010 pp.76-80